Analysis of the Potential of Sport Tourism as a Tourist Attraction in Lake Poso - Putra, Wijaya; Rahayu, Tandiyo; Wahyudi, Agung (Journal of Physical Education and Sports, 2021)
This study examined the possibilities for establishing sport tourism in Poso Regency, Central Sulawesi Province, with the goal of attracting tourists to Lake Poso. This research method is qualitative was using a case study approach, was using observation, interviews, and documentation to collect data, followed by SWOT analysis to analyze the data (Strengths, Weaknesses, Opportunities, Threats). The research results on the potential for developing sport tourism in Poso Lake, specifically the strength of sport tourism as unique natural tourist attractions, namely the lake’s edge resembling a white and golden yellow sandy beach, adequate facilities and infrastructure, and a short distance. Far from Poso Regency’s city center, Poso Lake’s weakness is licensed to open a business due to the conservation area, inadequate human resources, for the opportunities it has in developing sport tourism businesses, as well as threats that must be considered, namely the existence of culture or culture. Society’s traditions diminished. Conclusion: based on the results of the SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) conducted on the potential for developing sport tourism as a tourist attraction for Lake Poso, it can be concluded that Lake Poso have the potential to develop sport tourism as a tourist attraction.